Nigeria : Publication of Financial Sector Assessment Program Documentation -- Detailed Assessment of Implementation of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2013)
An assessment of the level of implementation of the International Organization of Securities Commissions (IOSCO) Principles in Nigeria was conducted as part of the International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP). The ongoing global financial crisis has reinforced the need for assessors to make a judgment about supervisory practices and to determine whether they are sufficiently effective. The assessment methodology provides a set of assessment criteria to be met in respect of each principle to achieve the designated benchmarks.